Answer: -437
Step-by-step explanation:
Answer:
Step-by-step explanation:
7*(7 + x+1) = 6*(x + 5 + 6) {Intersecting secant theorem}
7 *(x + 8) = 6*(x + 11)
Distributive property,
7x + 56 = 6x + 66
Subtract 56 from both sides
7x = 6x + 66 - 56
7x = 6x + 10
Subtract 6x from both sides
7x - 6x = 10
x = 10
Answer:
1636.25
Step-by-step explanation:
Answer:
observational study, you already know the outcome and you are doing it to take notes or learn while an experiment the outcome is unknown and you are seeing the reaction
Step-by-step explanation:
Hopes this helps??